The Impact of Audit Findings on Regional Losses in Local Governments of Regencies/Cities in Central Sulawesi Province - DIVYA, Sinta; DIN, Muhammad; JURANA, Jurana; MASDAR, Rahma (Journal of Governance, Taxation and Auditing, 2024)
This study aims to analyze the impact of audit findings on regional losses in the local governments of regencies/cities in Central Sulawesi Province. Employing a quantitative approach, the study utilizes secondary data from the Audit Results and Audit Results Summary provided by the Supreme Audit Board of the Republic of Indonesia. The research covers 13 regencies/cities in Central Sulawesi Province over the period from 2021 to 2023. To test hypotheses and evaluate the strength of relationships between variables, the study uses Partial Least Squares Structural Equation Modeling (SEM-PLS) analysis with WarpPLS 7.0 software. The findings reveal a positive and significant relationship between audit findings and regional losses, with a substantial coefficient value. These results suggest that an increase in audit findings correlates with higher regional losses. Therefore, local governments in Central Sulawesi Province should prioritize policies that promote legal compliance and strengthen internal control systems to minimize the risk of regional financial losses.